Effectiveness of Upskill, Reskill, and New Normal Skill of Tourism Business Personnel for the Prevention of Novel Coronavirus 2019 in Koh Samui, Surat Thani Province - รัชตาธนรัชต์, ทัศนมินทร์; วงค์เจริญ, ณีรนุช; เรืองอร่าม, สรรเพชญ (Journal of Health Science of Thailand, 2022)
This quasi-experimental research aimed to study the effectiveness of upskill, reskill, and new normal skill of tourism business personnel for the prevention of novel COVID-19. The samples were divided into 2 groups: (1) 274 tourism business personnel in Koh Samui, and (2) 20 related stakeholders. The research instruments included questionnaire, semi-structured in-depth interview and a program to develop upskill, reskill, and new normal skill. Data were analyzed by using descriptive statistics, paired t-test, independent t-test and content analysis. The research revealed that the mean score of competencies of tourism business personnel in experimental group after receiving the program was higher than before the program (Mean=2.23 vs 3.79, SD=0.77 vs 0.63) respectively. The mean scores of the competency of tourism business personnel between experimental group and control group after receiving the program were statistically significantly different at 0.01 level. The innovative value of application Samui Chana was at highest level (Mean=4.40, SD=0.60). This study indicated that the use of the program with application Samui Chana would enhance knowledge and skill on the prevention of the spread of COVID-19 among tourism business personnel.